yqhG Contributes to Oxidative Stress Resistance and Virulence of Uropathogenic Escherichia coli and Identification of Other Genes Altering Expression of Type 1 Fimbriae - Bessaiah, Hicham; Pokharel, Pravil; Habouria, Hajer; Houle, Sébastien; Dozois, Charles M. (Frontiers in Cellular and Infection Microbiology, 2019)
Urinary tract infections (UTIs) are common bacterial infections and the vast majority of UTIs are caused by extraintestinal pathogenic Escherichia coli (ExPEC) strains referred to as uropathogenic E. coli (UPEC). Successful colonization of the human urinary tract by UPEC is mediated by secreted or surface exposed virulence factors—toxins, iron transport systems, and adhesins, such as type 1 fimbriae (pili). To identify factors involved in the expression of type 1 fimbriae, we constructed a chromosomal transcriptional reporter consisting of lux under the control of the fimbrial promoter region, fimS and this construct was inserted into the reference UPEC strain CFT073 genome at the attTn7 site. This fimS reporter strain was used to generate a Tn10 transposon mutant library, coupled with high-throughput sequencing to identify genes that affect the expression of type 1 fimbriae. Transposon insertion sites were linked to genes involved in protein fate and synthesis, energy metabolism, adherence, transcriptional regulation, and transport. We showed that YqhG, a predicted periplasmic protein, is one of the important mediators that contribute to the decreased expression of type 1 fimbriae in UPEC strain CFT073. The ΔyqhG mutant had reduced expression of type 1 fimbriae and a decreased capacity to colonize the murine urinary tract. Reduced expression of type 1 fimbriae correlated with an increased bias for orientation of the fim switch in the OFF position. Interestingly, the ΔyqhG mutant was more motile than the WT strain and was also significantly more sensitive to hydrogen peroxide. Taken together, loss of yqhG may decrease virulence in the urinary tract due to a decrease in production of type 1 fimbriae and a greater sensitivity to oxidative stress.